Interethnic analyses of blood pressure loci in populations of East Asian and European descent. Issue 1 (December 2018) - Takeuchi, Fumihiko; Akiyama, Masato; Matoba, Nana; Katsuya, Tomohiro; Nakatochi, Masahiro; Tabara, Yasuharu; Narita, Akira; Saw, Woei-Yuh; Moon, Sanghoon; Spracklen, Cassandra N.; Chai, Jin-Fang; Kim, Young-Jin; et al.
Abstract Blood pressure (BP) is a major risk factor for cardiovascular disease and more than 200 genetic loci associated with BP are known. Here, we perform a multi-stage genome-wide association study for BP (maxN = 289, 038) principally in East Asians and meta-analysis in East Asians and Europeans. We report 19 new genetic loci and ancestry-specific BP variants, conforming to a common ancestry-specific variant association model. At 10 unique loci, distinct non-rare ancestry-specific variants colocalize within the same linkage disequilibrium block despite the significantly discordant effects for the proxy shared variants between the ethnic groups. The genome-wide transethnic correlation of causal-variant effect-sizes is 0.898 and 0.851 for systolic and diastolic BP, respectively. Some of the ancestry-specific association signals are also influenced by a selective sweep. Our results provide new evidence for the role of common ancestry-specific variants and natural selection in ethnic differences in complex traits such as BP. Blood pressure (BP) is a major risk factor for cardiovascular disease and more than 200 genetic loci associated with BP are known. Here, the authors perform discovery GWAS for BP in East Asians and meta-analysis in East Asians and Europeans and report ancestry-specific BP SNPs and selection signals.